(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
ABSTRACT This paper intends to present the experiences of former and current scholarship recipients of the Center for Afro-Brazilian Studies – NEAB/UDESC in different university extension operations at the Rondon Extension Center (NER/UDESC) in 2011, 2013, 2018, and 2019. We aim to reflect on our perception of the extension actions in which we participate within the scope of the university and to relate them to the workshops held at NER/UDESC. This way, we reflect on NEABian actions related to work that concerns racial equity and visibility of African and Afro-Brazilian cultures, under Federal Law 10.639/03 and in accordance with the National Curriculum Guidelines for Race and Ethnic Relations Education and for the Instruction of Afro-Brazilian and African History and Culture (2004), by emphasizing the importance of these actions in the region where Operation NER/UDESC is carried out. Our methodology in this paper is based on a critical reflection of the experiences lived by the participants in the indicated operations. The main results and conclusions point to the understanding that university extension is a powerful way to build and consolidate public policies for the democratization of knowledge in Brazilian higher education institutions and to promote racial equality.